The Impact of Inflation and Money Supply on Economic Growth in Jayapura City (2010–2022) - Eva Konjol; Elsyan Rienette Marlissa; Transna Putra Urip; Aldegonda Agung (Journal of International Conference Proceedings, 2024)
Economic growth is one of the benchmark indicators of the success of a country or a certain region, but economic growth is often hampered by problems that come as is often the case in the country and even the city of Jayapura itself there is inflation that occurs due to the influence of the volume of money supply in the community. The purpose of this study was to determine the effect of inflation and money supply on economic growth in the city of Jayapura in 2010-2022 using the path method (path analysis) developed using SPSS version 29.0. The results of this study concluded that based on the results of statistical analysis, it can be seen that the inflation variable (X1) has a sig value of 0.109 ? (0.05) where the coefficient (ß) is -0.440 and the variable money supply (X2) has a sig value of 0.001 ? (0.05) where the coefficient (ß) is 0.862 This shows that the inflation variable has a negative effect not significant and the JUB variable has a positive and significant effect on the rate of economic growth